KONSEP JIHAD DALAM AL-QUR’AN PRESPEKTIF SEMIOTIKA PEIRCE - Siti Mursida (Al Irfani: Journal of Al Qur'anic and Tafsir, 2021)
This research was conducted to seek and find the meaning of the signs and symbols in the term Jihad in the Qur'an based on Peirce's semiotic approach. This departs from the problem of narrowing the meaning of jihad which is more widely interpreted as war and crackdown against disbelief. However, if viewed in depth, the term jihad does not only contain a narrow meaning but contains broader meanings. By using Peirce's semiotic analysis knife, the author seeks to find the meaning attached to the term jihad in the Qur'an through the signs and symbols associated with the term. In the theory of semiotics, Charles Sanders Peirce is famous for his trichotomy (sign, object, and interpretant). This research is presented with a qualitative descriptive method to explain in depth through the data that has been found. From the results of this study, it can be concluded that the meaning and interpretation of the term jihad in several verses of the Qur'an does not only mean war, but has other meanings according to different contexts in each verse or surah. The meaning of jihad in general in this study there are three perspectives including First, jihad means da'wah (Jihad bi al-Qaul), Second, jihad means war (Jihad bi ash-Shilah). Third, jihad means charity (Jihad bi al-amal). This shows that jihad in the Qur'an has a broad and varied meaning.